2007
DOI: 10.1002/ceat.200700320
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mixing Times with Helical Ribbon Impeller for Non‐Newtonian Viscous Fluids Using an Advanced Imaging Method

Abstract: New results on mixing times for viscous Newtonian and non-Newtonian fluids being homogenized with a helical ribbon impeller are presented. In particular, a recently developed technique to determine the macromixing kinetics of an impeller in a transparent vessel was applied to investigate the effects of rheological properties on mixing times. Significant differences were observed in the mixing times for viscous Newtonian and non-Newtonian fluids. Based on the new data obtained in this work, a correlation incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…8–10 For each run, a colorimetric diagnosis was applied based on the image analysis captured by the webcam. More details about the tracer injection and colorimetric diagnosis are given elsewhere 9–11. In this work, we used the evolution of the level of brightness of the green color S , captured on a digital image representing the tank, to reconstruct the homogenization progress.…”
Section: Methodsmentioning
confidence: 99%
“…8–10 For each run, a colorimetric diagnosis was applied based on the image analysis captured by the webcam. More details about the tracer injection and colorimetric diagnosis are given elsewhere 9–11. In this work, we used the evolution of the level of brightness of the green color S , captured on a digital image representing the tank, to reconstruct the homogenization progress.…”
Section: Methodsmentioning
confidence: 99%
“…These geometries are almost universally employed in the blending of complex fluids, as they all possess low power draw in laminar flow. Direct torque measurement has been performed to obtain power curves in laminar flow (Fradette et al, 2007;Zhang et al, 2013;Fontaine et al, 2013), whilst flow measurements have been found using both intrusive methods such as Laser Doppler Anemometry (Jahangiri, 2007) and nonintrusive methods investigating opaque systems (Patel et al, 2014;Ihejirika and Ein-Mozaffari, 2007) and transparent varieties (Stobiac et al, 2014;Chhabra et al, 2007;Shervin et al, 1991). PIV measurements have become prevalent as the method of choice for non-intrusive determination of flow fields, owing to their non-intrusive nature and ease of application.…”
Section: Figure 1: Typical Butterfly Impellermentioning
confidence: 99%
“…Ozcan-Taskin & Nienow (1995) investigated flow fields and calculated mixing times for low elasticity fluids using a fibre-optic technique, additionally calculating mixing times in viscoelastic media, whilst a colorimetric method was adopted by Chhabra et al (2007).…”
Section: Figure 1: Typical Butterfly Impellermentioning
confidence: 99%